Numerical Study Effect of Secondary Air Mass Flow to Characteristics of Circulating Fluidized Bed Boiler - Ahmad Tarmizi; Giri Nugroho; Achmad Syaifudi; Bambang Sudarmanta (IPTEK Journal of Proceedings Series, 2018)
In this paper, computational study of Circulating Fluidized Bed (CFB) combustion is analyzed. The results are concern about volume fraction and velocity distribution along the boiler. Simulation result were present in velocity, volume fraction, and pressure profile in boiler. All discussed result are applicable to all type of fluidized bed boiler.This paper will concern about how fluidization and combustion occur in boiler. Simulation present in unsteady state, multiphase direction, k-ε standard turbulence model, species transport combustion model and DPM. In this simulation, fuel, air, and other input materials are defined by actual data from power plant operation. As a result of analysis, the variation of secondary air does affect the characteristics of fluidization and combustion in CFB system. The superficial velocity is found around 4.1 m/s. The pressure generated is about 6642.3 Pa in the windbox area, and in the middle furnace area about -868.6 Pa